Network security essentials applications and standards - Stallings, William (William Stallings books on computer and data communications technology, 2017)
For courses in Corporate, Computer and Network Security . Network Security: Innovations and Improvements Network Securities Essentials: Applications and Standards introduces students to the critical importance of internet security in our age of universal electronic connectivity. Amidst viruses, hackers, and electronic fraud, organizations and individuals are constantly at risk of having their private information compromised. This creates a heightened need to protect data and resources from disclosure, guarantee their authenticity, and safeguard systems from network-based attacks